Genetic mapping and candidate gene identification for key physiological traits associated with heat tolerance in wheat (Triticum aestivum L.) using a MAGIC population - Ananta Bag; Hari Krishna; Vinodh Kumar P.N; Shiwani Meena; Narayana Bhat Devate; Sudhir Kumar; Ravindra Patil; Uday Govinda Reddy; Amit Kumar Singh; Badal Singh; Neelu Jain; Pradeep Kumar Singh; et al. (PLoS ONE, 2026)
A comprehensive evaluation of 248 MAGIC population-derived wheat lines and their eight founder lines revealed significant genetic variation and adaptive diversity for key physiological traits- NDVI_1–3, SPAD chlorophyll content, canopy temperature (CT), and chlorophyll fluorescence (Fv/Fm UP and LW) under timely sown (TSIR) and late-sown (LSIR) irrigated conditions across multiple locations. Genotypes under TSIR exhibited higher canopy greenness, chlorophyll stability, and photosynthetic efficiency, whereas LSIR induced elevated CT and reduced SPAD, indicating genotypic differences in heat tolerance. Correlation and PCA analyses showed strong interrelationships among traits, with NDVI positively correlated with SPAD and Fv/Fm (r = 0.52-0.86) and negatively with CT (r = −0.13 to −0.60). PCA identified two principal adaptive axes- vigour/biomass (NDVI-CT) and pigment/stress (SPAD-Fv/Fm), explaining 65–82% of total variation. GWAS detected 54 significant marker-trait associations, predominantly on chromosome 5A, with major loci AX-95210025, AX-94980357, and AX-94448771 influencing NDVI, SPAD chlorophyll content, CT, and Fv/Fm (UP and LW). Favorable alleles enhanced canopy vigour and chlorophyll content while reducing CT, signifying integrated genetic control of photosynthetic resilience and thermal regulation. In-silico and gene regulatory network (GRN) analyses identified key heat-responsive candidate genes including TraesCS5A02G078000 (Heat shock cognate 70 kDa protein), TraesCS5A02G077900 (DnaJ co-chaperone), TraesCS1A02G098800 (DUF4408 domain protein), TraesCS7A02G143900 (Hydroxyproline O-arabinosyltransferase-like protein), and TraesCS7B02G083500 (Small heat shock protein) that regulate chlorophyll maintenance, PSII repair, and canopy cooling under stress. Collectively, this study elucidates the genetic and physiological basis of heat tolerance in the MAGIC population and identifies robust targets for marker-assisted selection and genomic improvement of thermotolerant wheat.